Challenges In Reforming Madrassa Education In Pakistan - Tajjalla Munir; Nimra Sajjad (Elementary Education Online, 2023)
The Madrassah education has remained an integral part of the education system of Pakistan. The difficult part is that the whole education system is reformed and changed yet Madrassah education has remained the same. The private schools are following the international standards of education while the madrassah education falls behind. The discussions of reforming the madrassah have been initiated but in practice, nothing has happened. So, it is significant to realize the challenges in reforming the madrassah education so the work can be done in the right direction. General Ayub tried to reform the madrasah by cutting the non-relevant subjects but he was considered liberal sand due to political instability the outcome of reforming madrassah education was not effective. While at the time of Zia-ul-Haq the education in Madaris was not reformed due to the mere fact that they thought the reforming of madrasah will mean becoming under the influence of government that they never wanted. In president Musharraf's time, the ulema rejected to reform the Madaris as the ordinance passed in 2005 made them feel that the madrassah is promoting extremism. Later on, the National Action Plan enforced the law for the registration of madrassah and its curriculum. The two major challenges are the government and the Madaris themselves. With the right coordination between the Madrassah and the government, the Reforming of madrassah can happen successfully.